Editorial - Deniz Evcik, (Archives of Rheumatology, 2010)
I would like to thank all those who have contributed their time and talents to making the Turkish Journal of Rheumatology a success. Special thanks to the associate editors and referees who have done excellent volunteer work on behalf of TJR. A list of those serving as referees over the past year is available at the end of the current issue. TJR receives approximately 100, new submissions each year and is able to accept only a relatively small percentage of them. The high submission rate, coupled with the low acceptance rate, helps to ensure that TJR considers and publishes excellent papers through selectivity. Currently there are limits on the number of pages that can be published annually. As such, it is the editorial team's desire to increase the number of pages in coming issues to decrease delayed publishing as well as reduce the waiting review and provide feedback in timely and constructive ways. In addition to full-length manuscripts, brief reports are welcome in TJR. The brief report format may be especially appropriate for empirically robust studies that are limited in scope, contain novel findings that need further confirmation or represent replications and extensions of prior published work. We encourage authors to submit brief reports as the TJR gets very few submissions. TJR has changed its policy on copyright statement now requesting it during the manuscript submission process. We are grateful to the authors who take the time to provide complete disclosure information and thus help to ensure the transparency of the publication process. As this is the last edition of TJR in 2010, I wish all readers a happy New Year. With my best regards! Prof. Deniz Evcik, MD Editor